2021
DOI: 10.7759/cureus.12599
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Cardiac Arrhythmias in Acute Myocardial Infarction Patients Undergoing Primary Percutaneous Coronary Intervention and Associated Outcomes During the First 24 Hours

Abstract: Background Acute myocardial infarction (AMI) is the most life-threatening manifestation of coronary artery diseases. The majority of deaths in AMI are due to arrhythmias. Therefore, the aim of this study was to evaluate the incidence and risk factors and outcomes of cardiac arrhythmias in AMI patients undergoing primary percutaneous coronary intervention (PCI) during the first 24 hours of the index hospitalization. Methodology This prospective observational study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 18 publications
5
10
0
Order By: Relevance
“…The mechanism is accelerated phase 4 depolarization of His-Purkinje fibers or ventricular myocardium. 15 AIVR is associated with cardiac pathology, such as after myocardial infarction, cardiomyopathies, electrolyte disturbances, and with digoxin intoxication, 1 , 2 , 3 but is also seen in patients without any cardiac abnormalities, and has been described in children, adolescents, and athletes. 4 , 5 , 6 , 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism is accelerated phase 4 depolarization of His-Purkinje fibers or ventricular myocardium. 15 AIVR is associated with cardiac pathology, such as after myocardial infarction, cardiomyopathies, electrolyte disturbances, and with digoxin intoxication, 1 , 2 , 3 but is also seen in patients without any cardiac abnormalities, and has been described in children, adolescents, and athletes. 4 , 5 , 6 , 7 …”
Section: Discussionmentioning
confidence: 99%
“…AIVR is associated with cardiac pathology and is observed in cardiomyopathies, after myocardial infarction, and during electrolyte disturbances or digoxin intoxication. 1 , 2 , 3 AIVR has also been reported as a benign rhythm variant without evidence of underlying cardiac pathology in children, adolescents, and athletes. 4 , 5 , 6 , 7 …”
Section: Accelerated Idioventricular Rhythmmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this study, Mhatre MA et al 13 reported that out of all, ventricular arrhythmias were observed among 33% of participants, among which VT was observed in 24% of the cases, VPB was observed in 8%, while 1% experienced ventricular bigeminy. On the other hand, Shah JA et al 15 conducted the study to assess the prevalence, risk factors, and consequences of cardiac arrhythmias among individuals with AMI receiving PCI within the initial 24 hrs of hospitalization and they observed higher occurrences of arrhythmias among 89.1% of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…2 Acute Myocardial Infarction(AMI) contributes to a significant proportion of mortality worldwide, much of which is attributed to life threatening arrhythmias. 3 Both supraventricular and ventricular arrhythmias can occur in AMI. Although, with the advances in treatment, the incidence of arrhythmias has reduced significantly but still life threatening arrhythmias occur in considerable proportion of AMI patients undergoing primary Percutaneous Coronary intervention (PCI).…”
Section: Introductionmentioning
confidence: 99%